Efficacy of Single Dose Ivermectin Against Strongyloides stercoralis Infection Among Primary School Children in Amhara National Regional State. (June 2020) - Hailu, Tadesse; Nibret, Endalkachew; Amor, Arancha; Munshea, Abaineh; Anegagrie, Melaku
Background: Ivermectin has been proven to be highly effective against Strongyloides stercoralis in some countries. However, its single dose (200 μg/kg) efficacy has not been proven up until now in Ethiopia. Objective: This study aimed to evaluate the efficacy of single dose ivermectin against S. stercoralis infection among school children. Methods: Stool sample was collected from April 2019 to December 2019 among 844 school children and screened by formol ether concentration, spontaneous tube sedimentation, Baermann concentration, and agar plate techniques. Single oral dose (200 μg/kg) ivermectin was given to 101 S. stercoralis –infected student and posttreatment diagnosis was done for 92 students after 2 weeks. Results: Of the total 92 S. stercoralis –infected students who took ivermectin treatment, 87 were negative with cure rate of 94.6%. No side effect of ivermectin was observed. Conclusion: Single dose ivermectin is an effective dose in uncomplicated chronic strongyloidiasis.